Genesis of the Bryophyte flora of fortification constructions in northwest Belarus (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The results of the research into Bryophyte flora diversity of fortification constructions in Grodno district (Grodno fortress, Molotov Line, northwest Belarus) are represented. The features of taxonomical, ecological and geographical structure of the Bryophyte flora were stated. The comparison of Bryophyte species in florogenetical aspect was carried out, first of all for the species of mountain origin. The comparative analysis of the bryoflora genesis of Grodno fortifications and the Carpathians bryophyte flora (as a depot of the appropriate species) was carried out.
Keywords: Bryophyte flora, fortifications, Carpathians, ecomorphs, geographical elements, flora genesis.